Elevated Neddylation Pathway Promotes Th2 Cells Infiltration by Transactivating STAT5A in Hepatocellular Carcinoma - Zhou, Lisha; Zhang, Luyi; Chen, Siyuan; Sun, Dongsheng; Qu, Jianhua (Frontiers in Oncology, 2021)
Neddylation is a process in which a ubiquitin-like molecule NEDD8 is conjugated to a lysine residue of the substrate protein via successive enzymatic cascade reactions. Inactivation of neddylation pathway triggers tumor cell apoptosis or senescence to suppress the tumor growth. So far, there has been limited research on the role of the neddylation pathway (NEDD8-UBE2M-RBX1 axis) in the immune response. In this study, we investigated the association between the neddylation pathway and immune function in HCC by comprehensively analyzing transcriptome and clinical data of HCC samples from TCGA database. The analysis showed that the mRNA expression of neddylation pathway components was up-regulated in HCC and increased with disease severity. Moreover, we observed that activated neddylation pathway was associated with enriched infiltration of T helper 2 (Th2) cells in HCC, while transactivation of STAT5A signaling may mediate this association. On the contrary, no significant correlation between the neddylation pathway and Th1 cells infiltration was identified. Taken together, these findings suggest a potential role of the neddylation pathway in promoting a shift in Th1/Th2 balance toward Th2-dominant immunosuppression. Hence, targeting neddylation pathway could serve as an attractive immunotherapy strategy for suppressing the development of Th2 cells.